Thickness-dependent mobility in two-dimensional MoS2 transistors. Issue 14 (17th March 2015) - Lembke, Dominik; Allain, Adrien; Kis, Andras
Abstract : The intrinsic mobility of two-dimensional (2D) semiconductors is easily masked by surface absorbates. We report here that after carful annealing, the room-temperature mobility of field-effect transistors (FETs) based on monolayer MoS2 is significantly higher than that of FETs based on two or three layers. Abstract : Two-dimensional (2D) semiconductors such as mono and few-layer molybdenum disulphide (MoS2 ) are very promising for integration in future electronics as they represent the ultimate miniaturization limit in the vertical direction. While monolayer MoS2 attracted considerable attention due to its broken inversion symmetry, spin/valley coupling and the presence of a direct band gap, few-layer MoS2 remains a viable option for technological application where its higher mobility and lower contact resistance are believed to offer an advantage. However, it remains unclear whether multilayers are intrinsically superior or if they are less affected by environmental effects. Here, we report the first systematic comparison of the field-effect mobilities in mono-, bi- and trilayer MoS2 transistors after thorough in situ annealing in vacuum. We show that the mobility of field-effect transistors (FETs) based on monolayer MoS2 is significantly higher than that of FETs based on two or three layers. We demonstrate that it is important to remove the influence of gaseous adsorbates and water before comparing mobilities, as monolayers exhibit the highest sensitivity to ambient air exposure. In addition, we study the influence of the substrate roughness and show that this parameter does not affect FET mobilities.